Smoking habit cessation in coronary patients. - Trigo, Miguel; Rocha, Evangelista (Acta Médica Portuguesa, 2002)
Assess the impact of coronary events in smoking cessation habits, and study the association between smoking habits and coronary artery disease.With a clinical structured interview, three groups were selected (n = 68), from the patients of the Cardiology Service of Hospital Militar Principal. Sample 1 was composed by patients with stable, and unstable angina (n = 18), sample 2 by patients with myocardial infarction (n = 26), and sample 3 by individuals with other cardiac disease (arterial hypertension, or valve disease) (n = 24). The individuals were aged between 48 and 75. The following statistical procedures were used: correspondence analysis, chi-square test (chi 2), and Fisher exact test.The association between smoking habits (non smoker, former smoker, and current smoker), and type of disease (angina, myocardial infarction, and arterial hypertension), was statistically significant [chi 2 (68) = 14.5; p = 0.006], and there was also a significant association between smoking habits and coronary artery disease [chi 2 (68) = 4.0; p = 0.045]. The category of ex-smokers and myocardial patients also showed significant association (Fisher exact test = 0.036).Previous myocardial infarction events constitute an experience of severe suffering and crisis, in which the patient accepts to stop smoking. We also confirm that smoking is a risk factor for myocardial infarction. Thus the objective of clinic interventions, aiming to promote the smoking cessation intentions, are important to promote this decision.